A Critical Look at The Good Life, Unifying the Philosophy and Psychology of Well-Being - Hamidreza Mahboobi Arani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Philosophers defend theories of what well-being is but ignore what psychologists have learned about it. Psychologists learn about well-being but lack a theory of what it is. In The Good Life: Unifying the Philosophy and Psychology of Well-Being, Michael A. Bishop marries these complementary investigations under what he regards as an “inclusive approach” and the result is a new framework for understanding well-being and the good life, that is “the network theory”. This theory identifies well-being with instantiating a self-sustaining network of positive feelings, attitudes, behaviors, traits, and accomplishments: a positive causal network. When doing well, you are embedded in a self-reinforcing web of positive internal and external states and events; when doing badly, you are caught in a "rut" or "vicious cycle" of negative interactions. Well-being is not just one component of a positive causal network, such as pleasure, desire-fulfillment, or virtuous activity. Well-being is the network itself. The current paper introduces the book with an emphasis on these two main foci. Then, it conclude with some objections to both methodology and substantive aspect of theory which mainly concerns its power of normativity.